Responses to 7 October, antisemitic discourse
1 online resource.
Keywords: "One of three volumes responding to the 7 October attack, Antisemitic Discourse, focuses on the ideology that motivated it and the antisemitism that shaped many responses to it. It examines the provenance of the Jew-hatred, from English history to Palestinian Islamism; from toxic 19th century 'Jewish Question' rhetoric to the perversion of the Trotskyist tradition that allowed parts of the left to embrace antisemitism. It includes Howard Jacobson's lecture of 22 October on antisemitism and it focuses on what was significant about this attack. There is discussion from Britain, Germany, Poland and Norway; and a linguistic account of responses. This work will appeal to scholars, students and activists with an interest in antisemitism, Jewish studies and the politics of Israel"--